Countering Piracy in the Modern Era - Chalk, Peter; Smallman, Laurence; Burger, Nicholas (RAND Corporation, 2023)
In March 2009, the RAND Corporation convened a small group of experts from the U.S. government, allied partner nations, the maritime industry, and academic organizations to discuss piracy in the modern era. Participants concluded that mitigating the complex nature of maritime crime requires the input of all stakeholders--state, national, private, and nongovernmental--and must embrace measures beyond the reactive deployment of naval assets.